Fabrication of micro-optical lenses for fiber optics applications - Pradeep Kumar Chandran. (2008)
Optical fibers are being used in a wide range of applications such as in communication, imaging, sensors and so on. In communication and imaging applications, the optical fiber is coupled to a light source, such as laser diode or light-emitting diode. It is desirable to have all the light from the source to enter the optical fiber but unfortunately this is not so. A way to solve this problem will be to use a microlens to focus the light into the fiber end. The shape of the fiber end face is modified so that it can serve as a lens. The fiber end face can be made spherical, tapered, conical or hemispherical. Also, such fiber lenses fabricated on the tip of the image fiber can make an efficient imaging lens-fiber system